Mitchell–Riley Syndrome: Improving Clinical Outcomes and Searching for Functional Impact of RFX-6 Mutations - Passone, Caroline de Gouveia Buff; Vermillac, Gaëlle; Staels, Willem; Besancon, Alix; Kariyawasam, Dulanjalee; Godot, Cécile; Lambe, Cécile; Talbotec, Cécile; Girard, Muriel; Chardot, Christophe; Berteloot, Laureline; Hachem, Taymme; et al. (Frontiers in Endocrinology, 2022)
Aims/hypothesis: Biallelic mutations of the gene encoding the transcription factor RFX6 bring about the rare Mitchell-Riley syndrome (MRS) that appears in newborns as neonatal diabetes due to pancreatic hypoplasia, gallbladder agenesis, duodenal atresia and severe chronic diarrhea. So far, sixteen cases have been reported, in which such a condition represents a poor prognosis in terms of mortality and quality of life. This study discusses the disease course and the intensive clinical management of 4 new cases of MRS that survived over the first 2 years of life. Moreover, it demonstrates how the mutations impair RFX6 function. Methods: Clinical records were analyzed and described in detail. The functional impact of two RFX6R181W and RFX6V506G variants was assessed by measuring their ability to transactivate Insulin transcription and genes that encode the L-type calcium channels required for normal pancreatic beta-cell function. Results: All four patients were severely small for gestation age (SGA) and prenatally diagnosed with duodenal atresia. On the first two days of life, they presented neonatal diabetes for which they received intravenous insulin therapy before switching to subcutaneous insulin pump therapy. The patients faced recurrent hypoglycemic episodes which were exacerbated through disconnection of parenteral nutrition. Frequency and severity related to these episodes were reduced by switching to sensor-augmented insulin pump therapy with a predictive low-glucose suspension system. The tapering of parenteral nutrition proved to be difficult, therefore a step-wise approach was important to a successful introduction of enteral feeding. Two mutations causing MRS have been reported, a homozygous p.Arg181Trp mutation in two patients and a new compound heterozygosity in a third one. The RFX6V506G and RFX6R181W mutations failed to transactivate Insulin expression and genes, encoding subunits of the L-type calcium channels required for normal pancreatic beta-cell function. Conclusions/interpretation: Multidisciplinary and intensive disease management have proved to improve clinical outcomes in MRS, including adjustment of parenteral/oral nutrition progression in association with advanced diabetes technologies. A better understanding of RFX6 function, in both intestine and pancreas, throughout development and physiology may break ground for new therapies, particularly regarding the use of drugs that modulates the enteroendocrine system.